2000
DOI: 10.1097/00007632-200007150-00022
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Secondary Spinal Cord Injury

Abstract: The outcome of spinal cord injury depends on the extent of secondary damage produced by a series of cellular and molecular events initiated by the primary trauma. This article reviews the evidence that secondary spinal cord injury involves the apoptotic as well as necrotic death of neurons and glial cells. Also discussed are the major factors that can contribute to cell death, such as glutamatergic excitotoxicity, free radical damage, cytokines, and inflammation. The development of innovative therapeutic strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
148
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(158 citation statements)
references
References 52 publications
2
148
0
5
Order By: Relevance
“…Secondary damage has been shown to induce the excessive release of excitatory amino acids and to cause intracellular calcium overload, the induction of free-radical-induced lipid peroxidation, and apoptosis (programmed cell death) 24,47 . Apoptosis is an actively regulated response that occurs after various cells have been subjected to external or internal stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary damage has been shown to induce the excessive release of excitatory amino acids and to cause intracellular calcium overload, the induction of free-radical-induced lipid peroxidation, and apoptosis (programmed cell death) 24,47 . Apoptosis is an actively regulated response that occurs after various cells have been subjected to external or internal stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is an actively regulated response that occurs after various cells have been subjected to external or internal stimuli. Recent experimental studies and clinical observations have revealed that spinal cord lesions are greatly exacerbated by apo ptosis 10,12,13,15,18,19,[22][23][24] . However, the molecular and cellular mechanism of apoptosis is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Secondary degeneration is one of the main pathological events following spinal cord injury (SCI). Attenuation of secondary degeneration has been considered critical to the outcome of the patients of SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation of secondary degeneration has been considered critical to the outcome of the patients of SCI. Although various pharmacological strategies, such as administrations of protein synthesis inhibitors, free radical scavengers, gangliosides and NMDA receptor antagonists, [3][4][5][6] have been developed to reduce secondary injury, only high-dose systemic administration of methylprednisolone within 8 h after injury is proved clinically useful for human SCI. [7][8][9] However, the use of methylprednisolone is effective only within a relatively narrow time window of 8 h after SCI, which is often impossible in many places around the world.…”
Section: Introductionmentioning
confidence: 99%